(untitled) (Journal of Atomic and Molecular Sciences, 2010)
We theoretically examine thickness and wavelength dependence line-shape of four-wave-mixing (FWM) spectroscopy in micrometric thin atomic vapors whose thickness L is assumed to be 10,30,50,80 and 100 μm respectively. It is found that a narrow centre (Dicke-narrowing) persists for all cases, while wings are broadened as the thickness of the vapor increases or the pump wavelength decreases comparing to the probe wavelength. This type of spectrum is due to the modified velocity distribution and polarization interference from different ensemble of atoms in a confined situation.